Characterization of Codonopsis Radix with Agro-product Geographical Indication products ‘‘Tanchang Dangshen’’ according to the analyses of elements and bioactive compounds combined with ecological factors - HOU, Jia; GUO, Hongru; LU, Guodi; WANG, Mingwei; DU, Tao (Food Science and Technology, 2024)
‘‘Tanchang Dangshen” codonopsis radix is a high-quality protected agro-product geographical indication (AGI), mainly grown in Gansu Province, China. In this study, combining multivariate analysis techniques with bioactive constituents and mineral elements, the differences between AGI-labeled “Tanchang Dangshen” codonopsis radix and adulterations from other geographical origins were investigated. Furthermore, the relationship between the chemical or mineral element characteristics of “Tanchang Dangshen” and its soil and climatic factors of geographical origin area was also explored. Using partial least square discriminant analysis, “Tanchang Dangshen” and the other codonopsis radix, with a similar botanical origin, were grouped according to mineral elements, especially the contents of potassium, selenium, and nickel. The environment with low temperatures was more conducive to the accumulation of potassium, which is the most abundant element of codonopsis radix. Soil factors, such as soil pH, soil organic matter, and soil nutrients, had an impact on the contents of trace elements it contains, i.e., nickel and selenium, which helped elucidate the relationship between the characteristics of high-quality AGI-labeled “Tangchang Danshen” and its geographical origin.